Pengaruh Latihan Jarak Bertahap dan Tetap terhadap Free throw Pemain Bolabasket Putri SMP Negeri 1 Ambarawa - Ajeng Satria Dewi; Aris Mulyono (Universitas Negeri Semarang, 2023)
This study aims to determine the effect of training using the gradual and fixed distance method on the results of free throws for basketball extracurricular participants at SMP N 1 Ambarawa, intended to determine which training method has a better effect on the results of shots free throw. Uses an experimental method with a two-group pre-test and post-test design. The instrument used is a shot free throw 10 times. The data analysis technique used a t-test. The results of the analysis show that: (1) There is an effect of training using the gradual distance method on the results of shots free throw of basketball extracurricular participants at SMP Negeri 1 Ambarawa, with the results of data analysis obtained a significant value of 0.000 < 0.05, and a percentage increase of 20% (2) There is an effective practice using the fixed distance method on the results of shots free throw of basketball extracurricular participants at SMP Negeri 1 Ambarawa, with the value of the results of data analysis obtained a significance value of 0.043 < 0.05, and a percentage increase of 8%. Based on the result, shooting practice using the gradual distance method is better to improve the results of the free throw of the basketball extracurricular participants at SMP Negeri 1 Ambarawa, rather than shooting practice using the fixed distance method.